PENAMBAHAN AMPAS TAHU DAN TEPUNG TOMAT PADA PAKAN KOMERSIAL TERHADAP PERFORMA PUYUH (Coturnix coturnix japonica) PERIODE LAYER - Akram, Hisyam; Nur, Hanafi; sudrajat, deden (Jurnal Peternakan Nusantara, 2019)
The quail is one kind of poultries that can give the distribution of society interests in case of eggs providing.  There are kinds of research that related to feed aspect, one of them is the way to increase the quality of feed by adding tofu waste and tomato flour on commercial feed. The aim of this research is to review the influences of giving the tofu waste and tofu tomato flour on commercial feed toward quail performance (cortunix cortunix japonica) in layer period.  Complete randomized design with used by the following treatment P0 (Provision of commercial feed without tofu and tomato flour), P1 (Provision of commercial food with 2.5% tofu dregs and 2.5% tomato flour), P2 (Provision of commercial food with 5% dregs of tofu and 5% tomato flour and P3 (giving commercial food with 7.5% tofu waste and 7.5% tomato flour).The treatment was conducted to quail aged 35 days until 67 days old. The feed and drink was given by adlibitium (always available). Giving tofu waste and tomato flour does not affect the feed consumption, egg’s weight, feed convertion, depletion, and the production of quail’s egg in layer period.Key words : Quail performance of layer period, tofu waste, tomato flour,  commercial feed